Let $b$ be a symmetric bilinear form on a $k$-dimensional vector space $V_k(\mathbb{F}_q)$, with $char(\mathbb{F}_q)=2$ and $k$ odd. Theorem 3.15 of the book S. Ball, Finite Geometry and Combinatorial applications states that $$ V_k(\mathbb{F}_q)=E \oplus F, $$ where the restriction to $E$ of $b$ is an alternating form and $F$ is a non-isotropic one-dimensional subspace.

In Corollary 3.10, it says that a non-degenerate alternanting form $b$ on $V_k(\mathbb{F}_q)$ ($k=2r$ even) is, up to a choice of a basis, $$ b(u,v)=\sum_{i=1}^r(u_{2i-1}v_i-u_{2i}v_{2i-1}). $$

Now, in Corollary 3.16, it states that a non-degenerate symmetric bilinear form $b$ on $V_k(\mathbb{F}_q)$ ($k=2r+1$) is, up to a choice of a basis, $$ b(u,v)=\sum_{i=1}^r(u_{2i-1}v_i+u_{2i}v_{2i-1})+u_{2r+1}v_{2r+1}. $$ Why this last statement is true?


1 Answer 1


First, subtraction is the same as addition, since we work over a field of characteristic $2$.

Applying the theorem, we get $V=E\oplus\langle f\rangle$ with $b(f,f)\ne 0$ and $b|_E$ being alternating.

Then, by the previous corollary, we can choose an appropriate basis on $E$, and let $w\notin E$ be a nonzero element of $E^\perp=\{x\mid\forall e\in E:\,b(x,e)=0\}$, which should exist since $b$ is nondegenerate. (See below.)

Then we can write $w=e+\lambda f$ with some $e\in E$ and $\lambda\ne 0$, and so, using symmetricity of $b$ and characteristic $2$, $$b(w,w)\ =\ b(e,e)+2\lambda\, b(w,f)+\lambda^2\,b(f,f)\ =\ \lambda^2\,b(f,f)\ne 0$$ Since in $\Bbb F_{2^m}$ every element is square (because $x=x^{2^m}$), $b(w,w)=\alpha^2$ and we can choose the last basis vector as $\alpha^{-1}w$ to get the desired coordinate form.

Update: Finally, to prove that $b|_E$ is nondegenerate (which also implies the existence of such $w$), assume that $E\subseteq e^\perp$ for some nonzero $e$, and choose a complementary subspace $E'\subseteq E$ with $\langle e\rangle\oplus E'=E$
Then $\dim E'=2r-1$ is odd, so the alternating bilinear form $b|_{E'}$ must be degenerate, yielding another vector $e'\in E'$ perpendicular to whole $E$.

Because of nondegeneracy, $b(e,f)\ne 0$, and thus $b(e',f)=\lambda\,b(e,f)$ with some $\lambda\in F$, so $e'-\lambda e$ would be $b$-perpendicular to the whole space.

  • $\begingroup$ Why you get the desidered coordinate form? $$b(u,v)=b(\sum_{i=1}^{r}u_ie_i+u_{2r+1}w,\sum_{i=1}^{r}v_ie_i+v_{2r+1}w)$$ $$=\sum_{i=1}^r(u_{2i-1}v_{2i}+v_{2i-1}u_{2i})+\sum_r b(u_ie_i,v_{2r+1}w)+\sum_r b(u_{2r+1}w,v_ie_i)+u_{2r+1}v_{2r+1}b(w,w)$$. Why $b(w,e_i)=0$? $\endgroup$ Sep 15, 2021 at 12:02
  • 1
    $\begingroup$ Because we chose $w$ from $E^\perp$. $\endgroup$
    – Berci
    Sep 15, 2021 at 13:21
  • $\begingroup$ thank you. Why $\lambda$ is different from $0$? $\endgroup$ Sep 15, 2021 at 14:39
  • 1
    $\begingroup$ But, we don't know if $E^{\perp} \subseteq E$ or not. Morover, in order to apply the result about the alternating form on $E$, first we must prove that $b$ is also non-degenerate on $E$. $\endgroup$ Sep 15, 2021 at 14:58
  • 1
    $\begingroup$ Ok, I think I got it. Updated my answer. $\endgroup$
    – Berci
    Sep 16, 2021 at 20:28

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.